Requerimiento nutricional del cultivo de piña (Ananas comosus) y su importancia en el rendimiento - García Sotomayor, Alex David (2021)
This document deals with the nutritional requirement of the pineapple (Ananas comosus) crop and its importance in yield. The nutritional requirement is important for the development and growth of crops, because mineral nutrients have specific and essential functions for the metabolism of plantations. The conclusions determined that it is necessary to carry out soil analyzes on an annual basis, in order to determine the amount of nutrients that the pineapple crop requires for its normal growth and development; Foliar applications of Calcium, Boron and Zinc do not increase the concentration of total soluble solids; Fertilization in pineapple crops is carried out from the moment of sowing to the ground, later foliar fertilizations are also carried out until before floral induction; It is necessary to comply with the opportune moment of the application of fertilizers and in the optimal quantities for the plantation and the applications of Nitrogen, Phosphorus, Potassium, Calcium and Magnesium and Zinc, the latter in a single application per harvest, positively influence to increase the weight and size of the fruits, trees with higher plant height, higher% of brix degrees, increased yield and quality of the fruit.